2014
DOI: 10.1631/jzus.a1400113
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion and aggregation of single-walled carbon nanotubes in aqueous solutions of anionic surfactants

Abstract: Abstract:Understanding the dispersion and aggregation of carbon nanotubes (CNTs) in the aqueous environment are critical for the fate, bioavailability, and the environment and health risk assessment of them because the better suspended CNTs display a higher mobility and could transfer to a longer distance in the environment to possibly pose greater ecological and environmental risks. In this study, we have found that bulk single-walled carbon nanotubes (SWCNTs) could not be dispersed and stably suspended in wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Multiwalled carbon nanotubes were stabilized with SDBS for uniform dispersion in aqueous solutions; however, natural cations (Naþ, Kþ, Ca 2þ , and Mg 2þ ) may have altered steric/ electrostatic repulsion forces induced by surfactants, causing aggregation to occur [32]. Calculated MWCNT D. magna uptake rates were significantly different in moderately hard and hard freshwater (Table 1, x 2 ¼ 41.61, p ¼ 0.01).…”
Section: Study I: Mwcnt Bioaccumulation and Uptakementioning
confidence: 99%
“…Multiwalled carbon nanotubes were stabilized with SDBS for uniform dispersion in aqueous solutions; however, natural cations (Naþ, Kþ, Ca 2þ , and Mg 2þ ) may have altered steric/ electrostatic repulsion forces induced by surfactants, causing aggregation to occur [32]. Calculated MWCNT D. magna uptake rates were significantly different in moderately hard and hard freshwater (Table 1, x 2 ¼ 41.61, p ¼ 0.01).…”
Section: Study I: Mwcnt Bioaccumulation and Uptakementioning
confidence: 99%
“…Similar phenomenon was observed for the stablized C 60 suspension , i.e., DOM could enhance the colloidal stability in Na + solution but decrease the stability significantly in Ca 2+ and La 3+ solutions. However, we observed that single-walled CNTs (SWCNTs) powders could not be stabilized in water even in the presence of surfactants, without the assistance of extreme agitation such as by sonication in dispersion (Yang et al, 2014). C 60 powders were also observed unable to be stably suspended in water or in DOM solution even with the assistance of sonication in dispersion .…”
mentioning
confidence: 99%
“…C 60 powders were also observed unable to be stably suspended in water or in DOM solution even with the assistance of sonication in dispersion . Moreover, the stably suspended nanoparticles may not remain stable in the presence of environmentally relevant cations (e.g., Na + , K + , Ca 2+ , Mg 2+ , and La 3+ ) (Hu et al, 2014;Yang et al, 2014;Zhang et al, 2014), especially once they were diluted (Yang et al, 2014). Dilution is a process commonly occurring once contaminants are released into the environment.…”
mentioning
confidence: 99%
See 2 more Smart Citations